A prospective study of influenza vaccination and time to pregnancy. Issue 27 (2nd June 2020) - Orta, Olivia R.; Hatch, Elizabeth E.; Regan, Annette K.; Perkins, Rebecca; Wesselink, Amelia K.; Willis, Sydney K.; Mikkelsen, Ellen M.; Rothman, Kenneth J.; Wise, Lauren A.
Highlights: Pregnancy planners are a priority group for influenza vaccination. The extent to which influenza vaccination affects fecundability is unclear. Influenza vaccination was common (47% of females and 37% of males). Our data indicate no adverse effect of influenza vaccination on fecundability. Abstract: Background: Although pregnancy planners are a priority group for influenza vaccination in the United States, little is known about the extent to which influenza vaccination affects fecundability. Methods: We analyzed data from Pregnancy Study Online (PRESTO), an ongoing preconception cohort study of North American pregnancy planners. During June 2013 to August 2019, 8654 female participants and 2137 of their male partners completed a baseline questionnaire and were followed until reported pregnancy, fertility treatment initiation, loss to follow-up, or 12 menstrual cycles of attempt time, whichever came first. At baseline, male and female participants reported whether they received an influenza vaccination in the past year and the date of vaccination. We used proportional probabilities regression models to estimate fecundability ratios (FR) and 95% confidence intervals (CI) comparing those who did and did not report influenza vaccination, adjusting for demographics, anthropometrics, behavioral factors, and medical history. Results: Influenza vaccination in the past year was more common among female participants than male participants (47% vs. 37%). FRs were 1.04 (95% CI: 0.98–1.10) for female vaccination and 1.03 (95% CI: 0.93–1.14) for male vaccination. Among the 2137 couples with complete data on both partners, for 40% neither partner was vaccinated, 23% had female-only vaccination, 9% had male-only vaccination, and in 28% both partners were vaccinated. Compared with couples in which neither participant was vaccinated, FRs were 1.13 for female-only vaccination (95% CI: 0.99–1.29), 0.94 for male-only vaccination (95% CI: 0.78–1.12), and 1.07 when both partners were vaccinated (95% CI: 0.94–1.21). When restricted to recent vaccination before peak influenza season, results were similar. Conclusions: Our data indicate no adverse effect of influenza vaccination on fecundability.